Mengurai Kompleksitas Hubungan Islam, HAM dan Barat - Supiyanto Abdi (Universitas Islam Indonesia, 2002)
Based on explanation regarding the complex relationship between Islam, Human Rights and West, this article discusses and offers two important main points: (i) the respecting for human rights is gracefulness ideal not for Islam only but also for all of religion and human kind, (2) the best paradigm of International relationship and especially between Islam and west is not clash or conflict but dialogue approach. In term of dialog, West on the one hand does not view Islam in zero-sum opposition to ward its values and civilization. In many cases covering the notions of humanity that stated in Human Rights Declaration of United Nation Organization, Islam and West have many similarities. Particularly the values of Islam that ever applied in the golden age of Islam. On the other hand, Moslem does not trap and regard western in this regard.